Effects of anti-miR-182 on TSP-1 expression in human colon cancer cells: there is a sense in antisense?. (November 2013) - Amodeo, Valeria; Bazan, Viviana; Fanale, Daniele; Insalaco, Lavinia; Caruso, Stefano; Cicero, Giuseppe; Bronte, Giuseppe; Rolfo, Christian; Santini, Daniele; Russo, Antonio
<x xml:space="preserve">Abstract</x> Objective: miRNAs are attractive molecules for cancer treatment, including colon rectal cancer (CRC). We investigate on the molecular mechanism by which miR-182 could regulate thrombospondin-1 (TSP-1) expression, a protein downregulated in CRC and inversely correlated with tumor vascularity and metastasis. Background: MicroRNAs are small non-coding RNAs that regulate the expression of different genes, involved in cancer progression, angiogenesis and metastasis. miR-182, over-expressed in colorectal cancer (CRC), has like predictive target thrombospondin-1 (TSP-1), a protein inversely correlated with tumor vascularity and metastasis that results downregulated in different types of cancer including CRC. Results: We found that TSP-1 increased after transfection with anti-miR-182 and we showed that miR-182 targets TSP-1 3′UTR-mRNA in both cells. Moreover, we observed that anti-miR-182 did not induce significant variation of Egr-1 expression, but affected the nuclear translocation and its binding on tsp-1 promoter in HCT-116. Equally, Sp-1 was slightly increased as total protein, rather we found a nuclear accumulation and its loading on the TSP-1 promoter in HT-29 transfected with anti-miR-182. Conclusion: Our data suggest that miR-182 targets the anti-angiogenic factor TSP-1 and that anti-miR-182 determines an upregulation of TSP-1 expression in colon cancer cells. Moreover, anti-miR-182 exerts a transcriptional regulatory mechanism of tsp-1 modulating Egr-1 and Sp-1 function. Anti-miR-182 could be used to restore TSP-1 expression in order to contrast angiogenic and invasive events in CRC.